Preoperative IMRT for soft-tissue sarcoma of the extremities and trunk: low rate of wound complications. Issue 5 (September 2018) - Studer, Gabriela; Glanzmann, Christoph; Maduz, Franziska; Bode, Beata; Fuchs, Bruno
Abstract : Background: The Canadian prospective randomized NCIC SR2 trial tested the sequence of radiation and surgery for extremity soft-tissue sarcoma. The trial was conducted in the era before intensity-modulated radiation therapy (IMRT) was clinically available. Similar disease control after preoperative and postoperative non-IMRT was found. However, the preoperative non-IMRT arm showed significantly less (persisting) late-term effects but increased (transient) wound complication rates compared to the postoperative non-IMRT arm (35% vs. 17%, P = 0.01). Consequently based on these results, preoperative radiation therapy was considered the preferred approach. Currently IMRT, with its option for highly conformal dose distribution that translates into better normal tissue sparing, is used as the general standard for sarcoma radiation therapy in most patients. Our hypothesis was that a lower wound complication rate after preoperative radiation therapy might be achievable in the IMRT era. Methods: We prospectively assessed our preoperative IMRT cohort (n=67 consecutive patients) treated between March 2008 and March 2016 with respect to wound complication rates. Results: Fourteen of 67 (21%) externally referred patients with recurrent (n=1) or incompletely resected disease (n=13), and 53 treatment-naive patients underwent planned preoperative radiation after core biopsy. After mean/median 7.3/7 wk (3-12 wk), complete tumor resection was performed. Secondary revision was required in five of 67 (i.e., wound complication rate of 7%). Two local failures were observed so far. Conclusions: The presented results support our hypothesis that preoperative IMRT may lead to a reduced wound complication rate compared to that after postoperative and mainly preoperative non-IMRT techniques.